2007
DOI: 10.1080/02571862.2007.10634811
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration ofVitis viniferaL.cvsSunred Seedless and Muscat Supreme in response to soil water depletion and irrigation cutoff during berry ripening

Abstract: The effects of soil water depletion and irrigation cutoff during ripening on yield, quality and evapotranspiration (ET) of table grapes were studied to refine irrigation strategies needed during hot, dry summers. Six irrigation treatments were applied to two cultivars, viz. Sunred Seedless and Muscat Supreme, from the 1998/99 until 2000101 seasons in a field trial in the Hex River valley of South Africa. Grapevines of all treatments were irrigated with micro-sprinklers at 40% plant available water (PAW) deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 3 publications
5
11
0
Order By: Relevance
“…The ET of more frequently micro-sprinkler irrigated grapevines (T3) was almost invariably higher from September until April compared to those that received irrigation two times per week (T4). This trend confirmed earlier reports, which showed that ET of micro-sprinkler irrigated vineyards on horizontally orientated trellis systems increased as the irrigation frequency increases (Myburgh, 2003b;Myburgh & Howell, 2007b). High evaporation peaks occurring more frequently in the case of the T3 treatment caused higher ET compared to T4 (Myburgh, 1998).…”
Section: T4supporting
confidence: 81%
See 4 more Smart Citations
“…The ET of more frequently micro-sprinkler irrigated grapevines (T3) was almost invariably higher from September until April compared to those that received irrigation two times per week (T4). This trend confirmed earlier reports, which showed that ET of micro-sprinkler irrigated vineyards on horizontally orientated trellis systems increased as the irrigation frequency increases (Myburgh, 2003b;Myburgh & Howell, 2007b). High evaporation peaks occurring more frequently in the case of the T3 treatment caused higher ET compared to T4 (Myburgh, 1998).…”
Section: T4supporting
confidence: 81%
“…1). Similar trends were reported for a sandy soil in the Lower Olifants River region (Conradie & Myburgh, 2000) and a coarse sandy soil in the Hex River valley in the Western Cape (Myburgh & Howell, 2007b). Previous results showed that Y m values below ca.…”
Section: Soil Conditionssupporting
confidence: 74%
See 3 more Smart Citations